Respuestas

2013-08-30T03:42:43+02:00
1. 3x + 2x = 5x
2. 6x – 15x = –9x
3. 2 2 23x + 2x 3x − + = 5x 5x +2x
4. 2 2 2x 3x 2x − − −x =− − x 4x
5. 3 2 2 3 3 3 2 2 x 3x − − − 2x x 4 + x 5 + = x x 5x + − + 2x 4x −3x−x =3 2 = + − 6x 2x 4x
6. ( ) ( )2 2 2 2 2 − − − + = 3x 2x x 4x − + 3x 2x x 4x 2x 4x
7.
5 (x – 2) = 5x–10
8.–2 (3x – 9) = –6x+18
9.. –2x (3x – 9) = 6x2 +18x
10.9x6(– 5x4 + 10x3 – 3x2 – x + 3) = –45x10 +90x9 –27x8 – 9x7 +27x6
Espero Te Sirvan Saludos !!

2013-08-30T04:43:29+02:00
1. 3x + 2x = 5x
2. 6x – 15x = –9x
3. 2 2 23x + 2x 3x − + = 5x 5x +2x
4. 2 2 2x 3x 2x − − −x =− − x 4x
5. 3 2 2 3 3 3 2 2 x 3x − − − 2x x 4 + x 5 + = x x 5x + − + 2x 4x −3x−x =3 2 = + − 6x 2x 4x
6. ( ) ( )2 2 2 2 2 − − − + = 3x 2x x 4x − + 3x 2x x 4x 2x 4x
7.
5 (x – 2) = 5x–10
8.–2 (3x – 9) = –6x+18
9.. –2x (3x – 9) = 6x2 +18x
10.9x6(– 5x4 + 10x3 – 3x2 – x + 3) = –45x10 +90x9 –27x8 – 9x7 +27x6
Espero Te Sirvan Saludos !!